Synechococcus dynamics in the Levantine basin shelf waters (northeastern Mediterranean) - UYSAL, Z.; KOKSALAN, I. (Mediterranean Marine Science, 2010)
The abundance of picoplanktonic marine cyanobacteria Synechococcus was measured at weekly intervals over a period of one year in the northern Levantine basin shelf waters. Synechococcuswas found more abundant during summer and early autumn and least during winter. Significant increases in abundances mostly occurred during very low nutrient concentrations either a week or two weeks after the nutrient enrichments. Cells were distributed homogenously in the water column due to intense mixing observed during winter. Despite the homogenous cell distribution attained during late autumn and winter, the magnitude of variation in cell abundances among depths was found greatest during August and September. Cell concentrations ranged from a minimum of 6.4 x 103 to a maximum of 9.2 x 104 cells ml-1 with an annual mean level of 2.5 x 104cells ml-1 at surface. Below the surface, it ranged from a minimum of 5.6 x 103 to a maximum of 8.0 x 104cells ml-1 with an annual mean level of 2.1 x 104 cells ml-1 at 25 m depth. Compared to surface and 25 m depth, lowest levels were attained at 50 m. At this depth, cell counts ranged from a minimum of 5.4 x 103to a maximum of 3.2 x 104 cells ml-1 with an annual mean level of 1.4 x 104 cells ml-1. Based on Pearson-product moment correlation analysis, a highly significant correlation between Synechococcusabundance and ambient temperature was observed.